Peran KH. Muhsin Salim dalam Mentransmisikan Qira’at Sab’ah di Jakarta Selatan 1986-2012 - Fasya, Ali (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This research discusses how Kiai Muhsin Salim transmits the knowledge of Qira'at Sab'ah in South Jakarta using the agency theory introduced by Anthony Giddens. The issue addressed is the role of Kiai Muhsin Salim in the transmission of Qira'at Sab'ah in South Jakarta. The sources used include books, photographs, and interviews. This research employs a descriptive historical method and a social-intellectual approach. The results obtained reveal the significant role of Kiai Muhsin Salim in the development of Qira'at knowledge in Jakarta. First, he taught at his own house and in various forums and gatherings in Jakarta, as well as at institutions such as PTIQ and LBIQ. Second, he authored books on Qira'at Sab'ah to facilitate understanding. Third, he nurtured and trained his students, who are now spread across South Jakarta, West Jakarta, and South Tangerang, and have established their own Quranic institutions. Abstrak :Penelitian ini membahas bagaimana kiai Muhsin Salim dapat mentransmisikan Ilmu Qira’ah Sab’ah di Jakarta Selatan dengan menggunakan teori agensi yang diperkenalkan oleh Anthony Giddens. Permasalahan yang dibahas adalah mengenai peran kiai Muhsin Salim dalam transmisi ilmu qira’ah sab’ah di Jakarta Selatan. Sumber yang digunakan adalah buku-buku, foto, dan wawancara dengan narasumber. Penelitian ini menggunakan metode sejarah deskriptif dan pendekatan sosial-intelektual dalam melihat fenomena pengembangan langgam bacaan al-Quran tersebut. Hasil yang didapatkan adalah peran kiai Muhsin Salim dalam perkembangan ilmu qira’at di Jakarta sangat besar pertama, mulai dari mengajar di rumahnya, majelis-majelis yang ada di Jakarta dan di tempat mengajarnya, seperti PTIQ dan LBIQ. Kedua, Ia juga membuat buku tentang qira’ah sab’ah untuk mempermudah dalam segi pemahaman. Ketiga, mengkaderisasi murid-muridnya yang sekarang ini ada yang tersebar di Jakarta Selatan, Jakarta Barat dan Tangerang Selatan, yang mempunyai lembaga Al-Qur’annya sendiri.